Implementasi Peran Badan Pengawas Pemilu terhadap Penegakan Tindak Pidana Pemilu (Politik Uang) pada Penyelenggaraan Pemilu Tahun 2019 di Kabupaten Purworejo - Indriany, Wiwin; Achmad, Achmad (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
ABSTRACTThis study examines the Implementation of the Role of the Election Oversight Body (Bawaslu) Towards Election Crime Enforcement (Money Politics) in Organizing the 2019 Elections in Purworejo Regency. This research is an empirical legal research. The nature of this research is descriptive research. Data collection techniques used were interviews and qualitative data analysis. The results of the study describe the implementation of the role of the Election Oversight Body (Bawaslu) of Purworejo Regency in the enforcement of the election (money politics) criminal acts in the 2019 elections as well as the obstacles faced by the Election Supervisory Body (Bawaslu) of Purworejo Regency during the enforcement of election criminal acts (money politics) in elections in 2019.Keywords : election supervisory body; election crime; money politics.